Pulsed Laser Diode Based Wireless Power Transmission Application: Determination of Voltage Amplitude, Frequency, and Duty Cycle - Yigit, Hayri; Boynuegri, Ali Rifat (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2023)
Laser power transfer (LPT) is one of the leading technologies in long-distance power transmission with its advantages such as enabling high power transmission and suitability for mobile applications. The transmitter part, which includes the laser diode (LD) and the driving circuit, directly affects system efficiency. Continuous wave (CW) lasers are used in studies due to their high power and continuous radiation. However, one of the main disadvantage of the mentioned system is the high cost of LD. In this study, the use of pulsed LDs in LPT applications is proposed because of their small size and low cost. On the other hand, appropriate operating point of pulsed LD is missing information in the literature. In order to contribute literature with this information, pulsed LD is used for LPT, and the effects of driving voltage amplitudes, frequencies, and duty cycles are analyzed to demonstrate the importance of determining the appropriate operating point of the pulsed LD and the potential use of pulsed LDs in LPT.
Keywords: Power lasers; Receivers; Optical transmitters; Masers; Semiconductor lasers; Laser modes; Power transmission; Wireless power transfer; laser power transmission; laser diode; pulsed laser diode; DRIVER; Computer Science; Engineering; Telecommunications